Measurement of pavement macrotexture through digital image processing - doi: 10.4025/actascitechnol.v35i1.12808 - Specht, Luciano Pivoto; Khatchatourian, Oleg; Santos, Reginaldo Tudéia dos (Acta Scientiarum. Technology, 2012)
The texture data of roads and airport pavement are extremely important for reducing accidents, mainly in cases of wet surface. The texture measurement is essential to evaluate the driving quality, however the conventional processes (field tests) are expensive and cause traffic interruption. Â  The aim of the present study was to develop a practical procedure to measure the asphalt pavement macrotexture using image processing and to compare it with sand patch tests. The parameter selected to quantify the surface pavement condition was the image information content calculated by a FFT (Fast Fourier Transform) through modification in the light intensity among neighboring pixels, this modification is called spatial frequency. Seeking to contribute with traditional methods, the proposed procedure causes low interruption in traffic, being also fast, accurate, with good reproducibility, and low cost. In comparison with sand patch test, the image processing technique proved to be efficient, and suitable to be used to identify areas with texture problem, reducing the possibility of accidents. Â 